CONSTRAINTS IMPLEMENTATION OF GEOGRAPHY LEARNING PROCESS BASED ON CURRICULUM 2013 AT SENIOR HIGH SCHOOL (CASE STUDY IN BACKWARD REGIONS OF LEBAK REGENCY, BANTEN PROVINCE) - Rahmatia, Rahmatia (Indonesia University of Education, 2018)
One part of the territory of the Republic of Indonesia that has been difficult to carry out the education process in accordance with the Standards of the Learning Process based on the 2013 curriculum, especially in backward regions of Lebak Regency, Banten. The condition of backward regions which still has obstacles to accessing and organizing education based on the 2013 Curriculum. Thus, the successful implementation of the 2013 Curriculum in backward regions would be a challenge to implement it appropriately and in accordance with established standards. This study aims to determine constraints implementation of geography learning process based on Curriculum 2013 at senior high school. This research uses qualitative approach with descriptive method. The principal participants in this study were Geography teachers at Senior High School who have implemented the Curriculum 2013 in backward region of Lebak Regency, Banten. Meanwhile, the participants of the base are learners and academic supervision. The research instruments are observation, interview, and document review.